Gravity - Gerritsen, Tess. (New York : Pocket Books, 1999)
One of the experiments Dr. Emma Watson carries into space harbors a deadly virus which infects the space statiion crew and now threatens earth's population.
730
Accelerated Reader AR
Keywords: United States. -- National Aeronautics and Space Administration -- Fiction; Women physicians -- Fiction; Microorganisms -- Research -- Fiction; Women astronauts -- Fiction; Communicable diseases -- Fiction; Space stations -- Fiction; Suspense fiction; Medical novels